Survey of UAV motion planning. Issue 1 (3rd May 2020) - Quan, Lun; Han, Luxin; Zhou, Boyu; Shen, Shaojie; Gao, Fei
Abstract : Motion planning is a vital module for unmanned aerial vehicles (UAVs), especially in scenarios of autonomous navigation and operation. This survey delivers some recent state‐of‐the‐art UAV motion planning algorithms and related applications. The logic flow of this survey is divided as the path finding, which is the front‐end of most motion planning systems, and the trajectory optimisation, which usually serves as the back‐end. Motivation, methodology, problem formulation and derivation are given in this survey, in detail. Finally, a section about real‐world applications is given, where roles and effectiveness of most popular motion planning methods are revealed.